On Certain Type of Difference Sequence Spaces Defined by Φ-Function - Ghimire, Jhavi Lal; Pahari, Narayan Prasad (Journal of Nepal Mathematical Society, 2022)
So far a large number of research works have been studied and investigated in basic sequence spaces c0, c, and l∞. In this present work, we introduce the difference sequence spaces W0(∆, f), W(∆, f) and W∞(∆, f) defined by non-negative real-valued Φ- function on R and study some of their topological properties defined by the paranormed structure on these spaces.